Facilitators of, and barriers to, prostate cancer screening uptake: A descriptive phenomenological study of adult men in Namibia - Nestor Tomas; Festus Meyambeko Benyamin (BMC Urology)
Abstract Background Prostate cancer poses a significant health risk for aging men, with a higher prevalence observed in individuals aged 40 and above. The objectives of this study were to describe the facilitators of, and barriers to, prostate cancer screening among men between the ages of 50 and 70. Methods The study employed a qualitative descriptive phenomenological design. Data were collected at the oncology and urology departments of an intermediate hospital in Oshana region, Namibia using a semi-structured interview guide. Individual, face-to-face interviews were held between September and October 2022, after which the data gathered were analyzed thematically following Colaizzi’s 7-step method. Results Fifteen (15) participants took part in this study. The two major themes that were generated were: (1) Value of early detection, which described the participants’ perceptions regarding the facilitators of prostate cancer screening; and (2) Potential threats to PCa screening, which described the participants’ perceptions regarding the barriers to taking up cancer screening. Conclusions The study revealed modifiable barriers to PCa screening, including fear of stigmatization, lack of knowledge, and insufficient screening access, as well as facilitators that can be strengthened for successful prostate cancer screening, such as advanced age, history of prostate cancer, and social support. These findings emphasize the need to implement gender-specific campaigns that address masculinity, lack of knowledge, and cultural stigmatization.